2018
DOI: 10.1001/jamadermatol.2018.2027
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab Treatment of Very Severe Refractory Atopic Hand Eczema

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…A 72‐year‐old female patient with >35 year history of CHE achieved complete clearance in 6 weeks, a 65‐year‐old female patient with >10 year history of CHE achieved 90% improvement in 6 weeks, and a 48‐year‐old male with 9‐year history of CHE achieved 80% improvement in 3 months, based on investigator subjective improvement (Zirwas, ). In a separate report, a 50‐year‐old female with an 18‐year history of severe atopic CHE refractory to potent TCS, psoralen UV‐A, cyclosporine, alitretinoin, and tacrolimus was successfully treated with dupilumab (loading dose of 600 mg subcutaneously and 300 mg once every 2 weeks) concomitantly with prednisolone 7.5 mg/day, for 12 weeks (Oosterhaven, Romeijn, & Schuttelaar, ). Her hand eczema severity index (HESCI) score improved from 244/260 (severe) at baseline to 11/360 (almost clear) at 16 weeks (Oosterhaven et al, ).…”
Section: Systemic Agentsmentioning
confidence: 99%
“…A 72‐year‐old female patient with >35 year history of CHE achieved complete clearance in 6 weeks, a 65‐year‐old female patient with >10 year history of CHE achieved 90% improvement in 6 weeks, and a 48‐year‐old male with 9‐year history of CHE achieved 80% improvement in 3 months, based on investigator subjective improvement (Zirwas, ). In a separate report, a 50‐year‐old female with an 18‐year history of severe atopic CHE refractory to potent TCS, psoralen UV‐A, cyclosporine, alitretinoin, and tacrolimus was successfully treated with dupilumab (loading dose of 600 mg subcutaneously and 300 mg once every 2 weeks) concomitantly with prednisolone 7.5 mg/day, for 12 weeks (Oosterhaven, Romeijn, & Schuttelaar, ). Her hand eczema severity index (HESCI) score improved from 244/260 (severe) at baseline to 11/360 (almost clear) at 16 weeks (Oosterhaven et al, ).…”
Section: Systemic Agentsmentioning
confidence: 99%
“…Initial case reports have shown favorable results for the use of dupilumab for hand dermatitis, suggesting there may be similarities in the pathophysiology of atopic dermatitis and hand dermatitis. Oosterhaven et al [3] first observed a female patient with very severe chronic atopic hand eczema and severe atopic dermatitis that had tried and failed alitretinoin, cyclosporine, azathioprine, mycophenolic acid, tacrolimus, and methotrexate showing “striking improvement” with dupilumab. At the beginning of treatment, her Hand Eczema Severity Index Score (HESI) was 244 out of 360, and by week 16, her hand eczema was “almost clear,” with a HESI of 16 out of 360.…”
mentioning
confidence: 99%
“…Patient 1, a lifeguard, presented with a BSA over 80%. Her dermatitis was most severe in a bathing suit distribution and under the bra elastic (Figure 1 (Zirwas, 2018) or no improvement with allergen avoidance (Oosterhaven, Romeijn, & Schuttelaar, 2018 Dermatitis of the back secondary to rubber accelerators suggested by more marked involvement underneath the patient's bra elastic (left) with resolution following dupilumab treatment (right)…”
Section: Resultsmentioning
confidence: 99%
“…Prior reports of severe, recalcitrant hand dermatitis responding to dupilumab, either noted no relevant allergens on patch testing (Zirwas, ) or no improvement with allergen avoidance (Oosterhaven, Romeijn, & Schuttelaar, ). Characteristics of the three patients presented here support the hypothesis that for our cases dramatic clinical improvement was based on dupilumab suppressing ACD reactions.…”
Section: Discussionmentioning
confidence: 99%